Effects of crosslinkers on morphological structure, washfastness and self-cleaning properties on titanium dioxide coated cotton yarn / Mirra Edreena Sallehudin - Sallehudin, Mirra Edreena (2023)
Titanium dioxide has an extraordinary photocatalytic activity and it effectively provides self-cleaning properties. However, the incorporation of HO2 nanoparticles into cotton faces a low surface area of the support and weak interactions between the fibre and nanoparticles. This makes the adherence of Ti02 nanoparticles on cotton weak and they eventually come off, especially after washing. Therefore, this study aimed to identify an optimal crosslinkers to coat Ti02 on cotton to improve its durability after washing and at the same time provide the self-cleaning properties. In this study, cotton yarn samples were treated with four different types of crosslinkers, which were 1,2,3,4butane tetracarboxylic acid (BTCA), polydimethylsiloxane (PS), succinic acid (SA),and polyacrylic acid (PAA) and were then dipped in 1% concentration of Ti02nanoparticles suspension.